Transfersomes as versatile and flexible nano-vesicular carriers in skin cancer therapy: the state of the art. (1st January 2017) - Rai, Shubhra; Pandey, Vikas; Rai, Gopal
ABSTRACT: Introduction: The skin acts as a barrier and prevents transcutaneous delivery of therapeutic agents. Transfersomes are novel vesicular systems that are several times more elastic than other vesicular systems. These are composed of edge activator, phospholipids, ethanol, and sodium cholate and are applied in a non-occlusive manner. Areas covered: This article covers information such as merits/demerits of transfersomes, regulatory aspects of materials used in preparation, different methods of preparation, mechanism of action, review of clinical investigations performed, marketed preparations available, research reports, and patent reports related to transfersomes. Expert opinion: Research over the past few years has provided a better understanding of transfersomal permeation of therapeutic agents across stratum corneum barrier. Transfersomes provides an essential feature of their application to variety of compositions in order to optimize the permeability of a range of therapeutic molecules. This is evidenced by the fact that there are several Transfersome products being processed in advanced clinical trials. It is noteworthy that a number of Transfersome products for dermal and transdermal delivery will gain a global market success in near future.